2015
DOI: 10.1097/qco.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

The future of antivirals

Abstract: Despite the recent advances, the BSAA field is still in its infancy. Nevertheless, the discovery and development of such molecules will be a key aim of antiviral research in the coming decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…As a proof of principle, we screened a set of compounds targeting RNA synthesis and found that cPol and vPol are differently inhibited by the 2΄F-2΄dNTP nucleoside analogues. This result could be exploited to develop novel influenza polymerase inhibitors (57). …”
Section: Discussionmentioning
confidence: 99%
“…As a proof of principle, we screened a set of compounds targeting RNA synthesis and found that cPol and vPol are differently inhibited by the 2΄F-2΄dNTP nucleoside analogues. This result could be exploited to develop novel influenza polymerase inhibitors (57). …”
Section: Discussionmentioning
confidence: 99%
“…Other powerful methods to be used in combination with glycomics and proteomics include RNA interference, CRISPR/Cas9 knockout, genome-wide haploid screens, cell-based arrays, drug-based approaches, and utilization of the microarray-characterized set of cells provided by US National Cancer Institute. We refer the reader elsewhere for further information on these methods [160][161][162][163][164][165][166]. A clear advantage of labelfree glycomics and proteomics technologies is, however, the minimal system perturbation in particular when untagged endogenous bait glycans and proteins are used.…”
Section: Alternative Approaches For Receptor Discoverymentioning
confidence: 99%
“…However, a broad catalogue of antivirals is required to make this strategy feasible, and this is only available for a small number of viruses such as HIV. Although some drugs can inhibit multiple viruses (e.g., nucleoside analogues with activity against both HIV and HBV [Debing, Neyts, & Delang, 2015;Mendes-Correa & Nunez, 2010]), viral enzyme-targeting drugs usually fail at protecting even against closely related virus species. By contrast, inhibition of cellular factors required for virus infection is expected to provide a higher barrier to the emergence of resistance.…”
mentioning
confidence: 99%
“…Because different viruses often exploit common cellular pathways, host proteins are promising targets for the development of broad-spectrum antiviral therapies (Martinez, Sasse, Bronstrup, Diez, & Meyerhans, 2015;Zhu, Meng, Wang, & Wang, 2015). Cellular kinases (Schor & Einav, 2018), cyclophilins (Dawar, Tu, Khattak, Mei, & Lin, 2017;Debing et al, 2015), and heat-shock proteins (Geller, Taguwa, & Frydman, 2012; represent potential candidates for such antiviral intervention.…”
mentioning
confidence: 99%